Parasitophorous vacuoles of Leishmania amazonensis-infected macrophages maintain an acidic pH. - Antoine, J C (1990)
Leishmania amastigotes are intracellular protozoan parasites of mononuclear phagocytes which reside within parasitophorous vacuoles of phagolysosomal origin. The pH of these compartments was studied with the aim of elucidating strategies used by these microorganisms to evade the microbicidal mechanisms of their host cells. For this purpose, rat bone marrow-derived macrophages were infected with L. amazonensis amastigotes. Intracellular acidic compartments were localized by using the weak base 3-(2,4-dinitroanilino)-3'-amino-N-methyldipropylamine as a probe. This indicator, which can be detected by light microscopy by using immunocytochemical methods, mainly accumulated in perinuclear lysosomes of uninfected cells, whereas in infected cells, it was essentially localized in parasitophorous vacuoles, which thus appeared acidified. Phagolysosomal pH was estimated quantitatively in living cells loaded with the pH-sensitive endocytic tracer fluoresceinated dextran. After a 15- to 20-h exposure, the tracer was mainly detected in perinuclear lysosomes and parasitophorous vacuoles of uninfected and infected macrophages, respectively. Fluorescence intensities were determined from digitized video images of single cells after processing and automatic subtraction of background. We found statistically different mean pH values of 5.17 to 5.48 for lysosomes and 4.74 to 5.26 for parasitophorous vacuoles. As for lysosomes of monensin-treated cells, the pH gradient of parasitophorous vacuoles collapsed after monensin was added. This very likely indicates that these vacuoles maintain an acidic internal pH by an active process. These results show that L. amazonensis amastigotes are acidophilic and opportunistic organisms and suggest that these intracellular parasites have evolved means for survival under these harsh conditions and have acquired plasma membrane components compatible with the environment.